Traditional and Critical Mentoring - Stoller, Aaron (Radical Teacher, 2021)
In the last fifteen years, critical theories of mentorship have become a small, but growing, thread in the mentoring literature. Despite this recent advancement, critical mentoring frameworks have yet to meaningfully impact the discourse of undergraduate peer mentoring. This essay is an attempt to address a twin concern that undergraduate peer mentoring programs need a more adequate theoretical basis for practice and that, in particular, the limited discourse on mentoring theory must be expanded to include a variety of critical theories. This paper identifies the core conceptual differences between traditional and critical theories of undergraduate peer mentorship and advances a grounded, critical framework for undergraduate peer mentoring.